2007
DOI: 10.1262/jrd.19035
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Estrous Behavior, Superovulatory Response and Grade 1 Embryo Sex Ratio in Superovulated Holstein Heifers

Abstract: Abstract. Abstract. In this study, we first attempted to determine whether the timing of artificial insemination affects the sex ratio of seven-day-old embryos in superovulated Holstein heifers. The superovulatory treatment consisted of eight decreasing doses of FSH for 4 days and 2 doses of PGF2α given with the last two doses of FSH. The superovulated heifers were given a GnRH analogue 48 h after the first PGF2α treatment and were artificially inseminated 48 h (n=10) or 56 h (n=8) after the first PGF2α treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Ideta et al (2007) reported that heifers bearing males had a significantly longer duration of oestrus, on the average, than those bearing females. These authors write: 'further, studies are needed to evaluate to what degree maternal hormone levels are related to oestrus duration and sex ratio'.…”
Section: Rosenfeldmentioning
confidence: 99%
“…Ideta et al (2007) reported that heifers bearing males had a significantly longer duration of oestrus, on the average, than those bearing females. These authors write: 'further, studies are needed to evaluate to what degree maternal hormone levels are related to oestrus duration and sex ratio'.…”
Section: Rosenfeldmentioning
confidence: 99%
“…Martinez et al [13] showed that the sex ratio of calves could be altered by the timing of AI, with early insemination during estrus resulting in more females and late insemination resulting in more males. However, we reported that changing the timing of AI did not influence the sex ratio of embryos collected from superovulated heifers [14]. We also reported that frequent transrectal examinations and/or blood samplings during the follicular phase increases the female sex ratio of bovine embryos, although the mechanism of this is unknown.…”
Section: Discussionmentioning
confidence: 90%
“…In cattle, females are preferred in the dairy industry. In our previous study [14], the proportion of female embryos collected from superovulated Holstein heifers that were frequently placed in stanchions and subjected to transrectal examination of the ovaries during the follicular phase tended to be higher than the expected 50% (66.7%, 26/39). The goal of the present study was to test the validity of this observation by using a greater number of superovulated and artificially inseminated heifers.…”
mentioning
confidence: 71%